2017
DOI: 10.1080/02699206.2017.1384853
|View full text |Cite
|
Sign up to set email alerts
|

Early communicative skills of children with Klinefelter syndrome

Abstract: Many studies reported the presence of language impairments in children and adolescents with Klinefelter syndrome (KS). However, the first stage of their language development has been scarcely studied. The present study aimed to describe the spontaneous communicative production of 18-month-old children with KS, in comparison with that of typically developing (TD) male peers, aiming to verify the existence of different early communicative skills in both vocal and gestural modality and to identify the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 22 publications
4
23
1
Order By: Relevance
“…Communication delays are evident from the first stages of language development (Samango‐Sprouse 2001, Zampini et al . 2018a, 2018b). For instance, Samango‐Sprouse (2001, Samango‐Sprouse and Law 2001) found the presence of a delayed babbling and phonological development in children with Klinefelter syndrome younger than 12 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication delays are evident from the first stages of language development (Samango‐Sprouse 2001, Zampini et al . 2018a, 2018b). For instance, Samango‐Sprouse (2001, Samango‐Sprouse and Law 2001) found the presence of a delayed babbling and phonological development in children with Klinefelter syndrome younger than 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…2003, Zampini et al . 2018a) and triple X syndrome (Linden et al . 1988), with the emergence of the first lexical items at around 18 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis is made by clinical examination and karyotype testing. Besides other characteristics, the phenotype includes infertility, hypogonadism, gynecomastia, cognitive disorders, especially in the language domain, besides psychiatric alterations [2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with KS tend to present difficulties in the regulation of emotions and behavior, affecting the relationship with their peers [2][3][4][5][6][7] . Babinet et al (2017) 8 suggested that disorders in social cognition are part of the phenotypic aspects of KS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation